Making sense of entrepreneurial opportunities - Hoyte, Cherisse Asha Shinelle (2015)
This thesis explores how entrepreneurial actors make sense of the entrepreneurial process as they transition from idea to enterprise. To explore this process, the thesis analyses the sensemaking and sensegiving processes experienced by prospective student entrepreneurs in a university incubator. Through addressing the following research question: “How do early-stage entrepreneurial actors make sense of the entrepreneurial process as they transition from having an idea to deciding to exploit it?”, this study explains how entrepreneurial actors transition from idea conceptualization to entrepreneurial opportunity exploitation and delineates their transition paths.